Modifying mesophyll conductance to optimise photosynthesis in crops - Salesse-Smith, Coralie E. (Burleigh Dodds Series in Agricultural Science, 2023)
Mesophyll conductance (gm), the ease with which carbon dioxide can diffuse into and through plant cells, is a promising target for improving photosynthetic rates in plants. Barriers including cell walls, membranes, liquid phases and the anatomy and orientation of the cells and their subcellular organelles impose resistances on carbon dioxide diffusion within leaves. Recent research has helped generate a comprehensive understanding of these resistances and we review efforts to alter and improve mesophyll conductance in plants through manipulation of the structure and composition of these barriers.